Formulation development and evaluation of layer-by-layer alginate/chitosan-coated microspheres loaded with simvastatin - Bernardo, Robert Joseph V.
Simvastatin (SMV) is a highly lipophilic drug that demonstrates poor bioavailability. This issue could be resolved through microencapsulation with the use of alginate (ALG) and chitosan (CS). We aimed to prepare and evaluate SMV-loaded microspheres coated with alternating layers of ALG and CS through LbL assembly The microspheres were then evaluated for size, size distribution, encapsulation efficiency (EE), and loading capacity (LC). The physicochemical characteristics of the microspheres were assessed using scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM/EDS), Fourier transform infrared (FTIR) spectroscopy, and differential scanning calorimetry. SMV-loaded microspheres were spherical, between 866.54 and 1109.28 μm in diameter. All microspheres showed a normally distributed size distribution. Results showed an EE from 19.51% to 27.71% and LC from 4.04% to 5.68%. SEM reveals that the surface of the microspheres with CS and ALG as the outermost layer was observed to be smooth and irregular, respectively. The elements C, O, N, and Ca were detected in the microspheres through the EDS, supporting the deposition of the polymers. The FTIR spectra show no chemical reactions between SMV and the polymers, indicating the compatibility among the materials. The thermograms reveal that the fabricated microspheres demonstrated a peak at approximately 139 °C, implying the successful encapsulation of SMV and that SMV loading did not affect the structures of both ALG and CS. This study offers some insights to develop multilayered microspheres to encapsulate SMV. We recommend conducting release profiling, X-ray diffraction, thermogravimetric analysis, stability study, and drug content analysis to further evaluate the physicochemical properties of the microspheres.